2022
DOI: 10.1016/j.cegh.2022.100994
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome among residents of different surgical specialties in a tertiary referral teaching hospital in Indonesia during COVID-19 pandemic

Abstract: Introduction Burnout is experienced frequently by residents, especially during COVID-19 pandemic. Impacts of the pandemic on clinical workload and training program of the residents has also resulted in burnout, which may impact their clinical performance and safety. Therefore, this paper aims to assess burnout syndrome among surgical residents in Indonesia during COVID-19 pandemic. Methods A cross-sectional survey was conducted on 120 surgical residents (from orthopedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Third, long work hour is an important factor associated with burnout in our study, yet the definition of long work hours associated with burnout remains unclear. Our previous study in Malang and other similar studies used 70 h/week as a cut-off point, but several studies showed that working >55 h/week was associated with medical conditions ( 17 , 46 49 ). Those gaps made our result may differ in studies with a different work hour classification, and a standardized work hour classification was needed in future studies to assess the true effect of the association between work hours and burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, long work hour is an important factor associated with burnout in our study, yet the definition of long work hours associated with burnout remains unclear. Our previous study in Malang and other similar studies used 70 h/week as a cut-off point, but several studies showed that working >55 h/week was associated with medical conditions ( 17 , 46 49 ). Those gaps made our result may differ in studies with a different work hour classification, and a standardized work hour classification was needed in future studies to assess the true effect of the association between work hours and burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the survey was conducted from August 1 to 31, 2021 using the Google Form platform, which was distributed to the representatives of each hospital together with information about the study procedures, ethical issues, and data collection. The required sample size was calculated using Cochran's formula estimating a 56.67% burnout prevalence in Saiful Anwar Hospital ( 17 ). Power was set at 80% and significance at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Learning pressure due to the high workload is exacerbated by online learning during the Covid-19 pandemic, which requires distance learning (Hypothesis 5). The impossibility of students to consult directly with lecturers and the implementation of large-scale social restrictions in Indonesia are factors that trigger the emergence of this condition (Daryanto et al, 2022;Moll et al, 2022;Novick et al, 2022). Various studies also show that the increase in academic stress experienced by students is a manifestation of the inability to manage and manage time and the workload given during lecture sessions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout dialami oleh 56% PPDS di Malang dan terkait dengan panjangnya jam kerja. 3 Pada penelitian lain, sekitar 15% PPDS mengalami ansietas dan 16% menderita depresi pada era COVID-19. 4 Kondisi stres juga ditemukan pada kelompok mahasiswa yang tidak terlibat dalam pelayanan kesehatan.…”
Section: Daftar Pustakaunclassified